A Patient with Recent Chest Discomfort—Ischemia or No Ischemia? Postsystolic Shortening Comes to the Rescue. Issue 9 (4th July 2013) - Fadel, Bahaa M.; Al‐Amro, Bandar; Al‐Admawi, Mohammed; Sergani, Hani; Alsoufi, Bahaaldin; Pergola, Valeria; Di Salvo, Giovanni
<x xml:space="preserve">Abstract</x> The diagnosis of myocardial ischemia in the emergency department can be challenging particularly in a patient in whom the chest discomfort has abated. Symptoms can be atypical, physical exam is often noncontributory, the electrocardiogram is usually nondiagnostic and cardiac enzymes remain normal. Thus, the decision for hospital admission or discharge can be quite difficult. Here, we describe such a patient in whom echocardiography with strain imaging identified the presence of postsystolic shortening (PSS) at the left ventricular apex. This suggested the likelihood of ischemic memory in the territory of the left anterior descending (LAD) artery. At coronary angiography a high grade stenosis was present in the proximal LAD artery. Our report highlights the role of echocardiography in the detection of myocardial ischemia and apical PSS as a marker of ischemic memory.